Towards green recovery of β-amylase from slurry of sweet potato (Ipomoea batatas) of VitAto variety via liquid biphasic system - Mohd Yusree, Farhana Iylia Fatinee; Peter, Angela Paul; Zulkifli, Nurul Ainina; Mohd Nor, Mohd Zuhair; Mohd Basri, Mohd Salahuddin; Mokhtar, Mohd Noriznan; Awasthi, Mukesh Kumar (Elsevier, 2022)
Liquid biphasic system (LBS) is a promising green extraction technology for the valorization of β-amylase from sweet potato slurry. In the present study, β-amylase was purified from sweet potato slurry in a polyethylene glycol-citrate liquid biphasic system. Its processing factors require refinement, and its green processing elements need to be assessed for this technology to be successfully applied in the downstream industry while meeting the sustainable development goals. This research's novelty is held by the potential of sweet potato slurry for the recovery of β-amylase and the assessment of green extraction technology on the optimized process. The findings show the increasing trend of the recovery yield, purification factor, and selectivity with the salt and polymer concentration increment. The optimized combination of factors was 60% citrate with 60% polymer, yielding a purification factor of 3.5087, a recovery yield of 78.24%, and selectivity of 3.9608. The optimized LBS was found to improve certain aspects of the green extraction concept. The potential of the LBS to be utilized for the green extraction of β-amylase from sweet potato slurry is proven in this study. This suggested a promising avenue to pursue the application of this separation method to purify biomolecules from the sweet potato slurry.